Peran Akhwat Bergerak Indonesia Dalam Kegiatan Sosial Dan Keagamaan - Sobar, Amin; Muslim, Muslim; Mahmudah , Mahmudah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The aim of the research is to describe the role of Indonesian mobile sisters in social and religious activities at the Khadijati Foundation. The research method is descriptive qualitative. Data collection techniques using interviews, observation, and documentation. Data processing techniques using reduction, data presentation, and conclusions. Data validity technique using triangulation. Research results: (1) role: compensation for orphans and poor people, Friday rounds, humanitarian activities, assistance for orphans and poor people in Palestine, and providing Qurbani for memorizing the Qur'an. (2) Supporting factors: synergy and partnership between sister communities, and use of social media platforms for social movements. Inhibiting factors: time flexibility, limitations on movement, donation cases. Conclusion: the role of the sisters in the foundation is running very well and has great benefits for society.